Modeling of resistivity and acoustic borehole logging measurements using finite element methods. (2021) - Pardo, David; Matuszyk, Paweł J; Puzyrev, Vladimir; Torres-Verdin, Carlos; Nam, Myung Jin; Calo, Victor M
No abstract available